2021
DOI: 10.1093/ajcp/aqab010
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Spectrum and Molecular Landscape of Myeloid Disorders Harboring SF3B1 Mutations

Abstract: Objectives SF3B1 mutations are the most common mutations in myelodysplastic syndromes (MDS). The International Working Group for the Prognosis of MDS (IWG-PM) recently proposed SF3B1-mutant MDS (SF3B1-mut-MDS) as a distinct disease subtype. We evaluated the spectrum and molecular landscape of SF3B1-mutated myeloid disorders and assessed the prognostication in MDS harboring SF3B1 mutations (MDS-SF3B1). Methods Cases were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 55 publications
9
5
1
Order By: Relevance
“…In this study, we evaluated the IWG-PM proposed SF3B1 entity criteria. We confirmed the favorable clinical outcome of SF3B1 entity similar to recently published studies [21,22]. Additionally, in line with Komrokji et al we observed a significantly longer OS of SF3B1 entity patients compared to SF3B1 non-entity patients, in contrast to Venable et al who did not observe significant differences in OS between SF3B1ent and SF3B1nent presumably due to the small cohort size [21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we evaluated the IWG-PM proposed SF3B1 entity criteria. We confirmed the favorable clinical outcome of SF3B1 entity similar to recently published studies [21,22]. Additionally, in line with Komrokji et al we observed a significantly longer OS of SF3B1 entity patients compared to SF3B1 non-entity patients, in contrast to Venable et al who did not observe significant differences in OS between SF3B1ent and SF3B1nent presumably due to the small cohort size [21].…”
Section: Discussionsupporting
confidence: 92%
“…SF3B1 mutations are frequently detected within MDS and associated with favorable prognosis [5][6][7]. In our WGS-based cohort of 734 MDS patients we identified 231/734 (31%) cases with SF3B1 mutations verifying known hotspots in K700, K666 and H662 [4,7,8,20,21] and confirming a heterozygous SF3B1 mutation status with high median VAFs (35%) across all entities. VAFs >30% were observed in 77% of SF3B1 mut samples.…”
Section: Discussionsupporting
confidence: 67%
“…However, it might be unidentified in others. Alternatively, SF3B1 mut CHIP or CCUS (clonal cytopenia with undetermined significance) may represent relevant precursor lesions of SF3B1 mut AML, in line with Venable et al, showing that SF3B1 mut cases comprise the full pathologic spectrum of myeloid disorders from CCUS to AML [14]. In SF3B1 mut s-AML patients, we frequently detected MECOM-r and RUNX1 mutations, both known AML driver genes [5].…”
Section: To the Editorsupporting
confidence: 87%
“…Indeed, MDS patients with a mutated SF3B1 genotype showed lower WT1 expression values than the WT counterpart. Because the expression of WT1 at normal levels is an indicator of a good prognosis, this result corroborates the role of SF3B1 status as a good prognosis marker [ 5 , 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 73%